2021
DOI: 10.2131/fts.8.81
|View full text |Cite
|
Sign up to set email alerts
|

Movento® 240SC (Spirotetramat) and Envidor® 240SC (Spirodiclofen) keto-enol insecticides induce DNA damage in <i>Drosophila melanogaster</i> ovaries

Abstract: Movento® 240SC and Envidor® 240SC are new insecticide derivatives of tetramic acid belonging to a keto-enol pesticide family. However, few studies have reported genotoxic effects in nontarget organisms. In the present study, the genotoxic effects of Movento® 240SC and Envidor® 240SC on Drosophila melanogaster ovaries were analyzed using the alkaline comet assay. Simultaneously, we determined the LD 50 for both insecticides. Virgin females were exposed to food at three sublethal concentrations (11.2, 22.4, 37.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The commercial keto-enol insecticides Movento ® 240SC and Envidor ® 240SC and their active ingredients (Spirotetramat and Spirodiclofen) have been shown to induce DNA damage in non-target organisms [ 12 , 14 ]. In a previous study, we reported that the commercial acaricides Movento ® 240SC and Envidor ® 240SC induce a significant increase in damage in the ovary DNA of wild-type Drosophila melanogaster (Oregon R) [ 17 ]. However, there were no reports on DNA damage response (DDR) pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The commercial keto-enol insecticides Movento ® 240SC and Envidor ® 240SC and their active ingredients (Spirotetramat and Spirodiclofen) have been shown to induce DNA damage in non-target organisms [ 12 , 14 ]. In a previous study, we reported that the commercial acaricides Movento ® 240SC and Envidor ® 240SC induce a significant increase in damage in the ovary DNA of wild-type Drosophila melanogaster (Oregon R) [ 17 ]. However, there were no reports on DNA damage response (DDR) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred microliters of each concentration were mixed with yeast to form a paste that was deposited in the bottom of Drosophila Genesee Scientific ((Wilford, Nottingham, UK) food vials. The concentrations of both insecticides that induced DNA damage in ovarian cells were reported in a previous study and used in three independent experiments [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen (2018) showed that SPT administration retarded the development of zebrafish embryos, induced oxidative stress, and reduced the activity and expression of target Acetyl CoA carboxylase, fatty acid synthesis, and sterol regulatory element associated genes. The findings obtained by González-marín et al ( 2021) showed that Movento® 240SC insecticide is a genotoxic agent in D. melanogaster ovaries because it increased the genotoxic parameters (tail length, tail moment, and tail intensity) in cell nuclei of D. melanogaster. According to Zhang et al (2015), SPT can cause low and moderate levels of DNA damage in earthworm coelomocytes and may represent possible biochemical and genetic toxicity to earthworms.…”
Section: Introductionmentioning
confidence: 96%